Ludivine Sarah Stewart, The regulation of AI-based migration technologies under the EU AI Act: (Still) operating in the shadows? - Narożniak, Agnieszka (Studia Prawa Publicznego, 2025)
Ludivine Sarah Stewart, The regulation of AI-based migration technologies under the EU AI Act: (Still) operating in the shadows? (Regulacja technologii migracyjnych opartych na sztucznej inteligencji w świetle unijnego Aktu w sprawie sztucznej inteligencji: Działając (nadal) w cieniu? „European Law Journal” 2024, vol. 30, no. 1–2, s. 122–135, https://doi.org/10.1111/eulj.12516